PEMETAAN LITERATUR KAPABILITAS DINAMIS PADA UMKM DI INDONESIA: TINJAUAN LITERATUR SISTEMATIS - Maulidan, Rahmat; Gunanjar, Imam; Ridwan Verinanda, Muhammad; Syahputra, Rico; Hardianti, Anisha (Universitas Prof. Dr. Hazairin SH, 2025)
This study presents a systematic analysis of the conceptual development of dynamic capabilities in the context of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. To remain competitive, MSMEs are required to possess a high level of adaptability. One relevant approach to explaining this adaptive capability is the concept of dynamic capabilities, which includes the abilities to sense, seize, and reconfigure. The objective of this study is to map the development of literature related to dynamic capabilities within the Indonesian MSME context and to identify existing conceptual and practical gaps. The research method employed is a Systematic Literature Review (SLR). Literature was collected from leading databases such as Google Scholar, DOAJ, Emerald, and SINTA using the Publish or Perish application, covering the period from 2020 to 2024. From the 49 selected articles, a process of screening, coding, and thematic analysis was conducted. The findings indicate that dynamic capabilities significantly contribute to the resilience, innovation, and performance of MSMEs. However, there remain inconsistencies in definitions and measurement approaches. Moreover, this study is limited to the MSME sector, which restricts the generalizability of the findings. The main contribution of this study is to provide a systematic mapping of recent literature and to propose future research directions and policy recommendations that support the strengthening of dynamic capabilities among MSMEs, particularly in the face of business environmental uncertainty.